G350(P) Biliary atresia: referral barriers within the community. (25th October 2020) - Alexander, EC; Burford, C; Thaxter, D; Davenport, M; Dhawan, A; Jain, V
Abstract : Aims: Biliary atresia (BA) is an idiopathic neonatal cholangiopathy, requiring Kasai Portoenterostomy (KP), to re-establish bile drainage. Failure of KP necessitates liver transplantation (LT). Earlier age at KP (<46 days) is associated with improved post-KP outcomes. Late referrals from the community (>100 days) often undergo primary LT. National guidelines state all term babies jaundiced after 14 days of age, to be referred for a conjugated bilirubin. The aim of this study was to identify referral pathways and barriers within the community for potential BA infants. Methods: A retrospective review of clinical notes, of 47 consecutive newly-diagnosed BA infants (Jan 2016-May 2018) at a specialised liver unit. Values expressed as median (range). Results: Forty-seven infants (22F:25M, 91% isolated BA and 9% syndromic BA), were included. Age of referral from community to liver unit was 30 days (5–238 days); 83% were referred before 46 days; 2 patients referred >100 days. Seventy-seven percent (36/47) of infant parents expressed concerns of jaundice at the 14-day community check, 19% (9/47) had jaundice recognised appropriately by secondary care whilst inpatient for other co-morbidities, and 2/47 infants were referred early (5 and 6 days) following antenatal ultrasound abnormalities. Seventy-five percent (27/36) of the concerned parents were falsely reassured by health professionals. Two thirds of these infants were breast/mixed-fed and 30% were dark-skinned. These 27 infants ended up being referred to the liver unit at 43 days (17–238 days), either by (i) persistent parental pressure (13) (ii) parental self-referral to A+E for jaundice (2) (iii) 6–8 week GP check (9) (iv) secondary care presentation for other comorbidities (3). Only 4/47 parents reported recognising stool was pale. No parent reported being shown a stool colour chart. Referral from community to liver unit admission was 3 days (0–28 days), and liver unit admission to KP was 8 days (2–48 days). Conclusion: Tighter regulation of the national jaundice guideline is required, to expedite referrals for potential BA from community to liver units, in turn, improving outcomes in this high-risk cohort of patients.